Review: Stockmen from Tekoa, Sycomores from Sheba: A Study of Amos' Occupations - Cathcart, Kevin J. (Journal of Semitic studies, 2006)
Stockmen from Tekoa, Sycomores from Sheba: A Study of Amos' Occupations Richard C. Steiner , (The Catholic Biblical Quarterly Monograph Series 36). The Catholic Biblical Association of America, Washington DC 2003. x + 158. Price: $10.50 paperback. ISBN: 0-915170-35-3